With no lysine kinase 3 (WNK3); A Target Enabling Package - Pinkas, D (University of Oxford, 2018)
A description of the materials and methods is included within the TEP datasheet. Kinases WNK1-4 regulate cation-chloride cotransporters via phosphorylation of SPAK and OSR1 and thereby control salt homeostasis, cell volume and blood pressure. Gain of function mutations in WNK kinases are found in Gordon’s hypertension syndrome suggesting the WNK pathway as a therapeutic target. WNK3 inhibition in particular has also been shown to reduce cerebral injury after Ischemic stroke. Here we present assays and crystal structures that define (i) the molecular basis for disease mutations; (ii) the multiple functional domains of WNK kinases and their protein interactions; (iii) the binding of small molecule kinase inhibitors and a potential allosteric pocket.